2015
DOI: 10.1371/journal.pone.0138815
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant 5’-CpG Methylation of Cord Blood TNFα Associated with Maternal Exposure to Polybrominated Diphenyl Ethers

Abstract: Growing evidence suggests that maternal exposures to endocrine disrupting chemicals during pregnancy may lead to poor pregnancy outcomes and increased fetal susceptibility to adult diseases. Polybrominated diphenyl ethers (PBDEs), which are ubiquitously used flame-retardants, could leach into the environment; and become persistent organic pollutants via bioaccumulation. In the United States, blood PBDE levels in adults range from 30–100 ng/g- lipid but the alarming health concern revolves around children who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 62 publications
1
24
0
2
Order By: Relevance
“…Above this threshold, there was a negative association between PBDE and CpG meth-future science group Effects of prenatal exposure to endocrine disruptors & toxic metals on the fetal epigenome Review ylation of TNF-α. Moreover, this effect appeared to be modified by the sex of the fetus, with the same pattern noted in females, but not males [97].…”
Section: Polybrominated Diphenyl Ethersmentioning
confidence: 62%
See 1 more Smart Citation
“…Above this threshold, there was a negative association between PBDE and CpG meth-future science group Effects of prenatal exposure to endocrine disruptors & toxic metals on the fetal epigenome Review ylation of TNF-α. Moreover, this effect appeared to be modified by the sex of the fetus, with the same pattern noted in females, but not males [97].…”
Section: Polybrominated Diphenyl Ethersmentioning
confidence: 62%
“…In light of the immune-related effects of prenatal PBDE exposure, the relationship between methylation of TNF-α and PBDE exposure was investigated in the Boston Birth Cohort [97]. Maternal serum levels were significantly associated with a decrease in CpG methylation of the promoter region of TNF-α in DNA isolated from cord blood.…”
Section: Polybrominated Diphenyl Ethersmentioning
confidence: 99%
“…Similarly, the CHAMACOS study, a longitudinal birth cohort study in California, found that maternal PBDE levels were significantly and differentially associated with weight changes in children at the age of 7 years based on sex 114. Another study, the Boston Birth Cohort, examined paired maternal cord blood samples and established that PBDE exposure may result in epigenetic modifications at the promoter region of inflammatory markers, thereby increasing the susceptibility to MetS 95. Therefore, while it remains to be determined whether PBDE exposure during pregnancy has a significant impact on subsequent metabolic perturbations, long-term data suggest that further studies are warranted.…”
Section: Household Exposuresmentioning
confidence: 99%
“…In the US, PBDE levels in adults range from 30 to 100 ng/g lipid and these values are typically higher in children 95. PBDEs measured in pregnant women have ranged between 2.44 and 258 ng/g lipid, while the median concentrations remain between 7.7 and 9.97 ng/g lipid 96,97.…”
Section: Household Exposuresmentioning
confidence: 99%
“…The increased gene expression of PPAR2 inducing adipocyte differentiation accompanied after BDE-47 exposure was related to a decreased methylation status of the PPAR2 promoter in 3T3-L1 cells[34]. The cohort study to examine the impact of prenatal exposure to PBDEs showed decreased cord blood TNF- promoter methylation associated with high maternal BDE-47 exposure[35]. Recent study has shownthe promoter of adiponectin known to play an important role in energy homeostasis is hypermethylated in obese mice.…”
mentioning
confidence: 99%